How rural tourism development affects farmers’ livelihood resilience: based on comprehensive survey data of rural revitalization in China - Niu, Jinlan; Zhou, Yuxi (Frontiers in Sustainable Food Systems, 2025)
Many rural areas regard the tourism livelihood strategy as an essential breakthrough to overcome poverty and improve the lives of farmers. Studies have explored the income increasing effect of rural tourism on farmers’ families, but few have focused on the impact of rural tourism on farmers’ livelihood resilience under the requirements of rural sustainable development. The purpose of this paper is to explore the impact of rural tourism development on the livelihood resilience of rural households, using 987 households from the China Rural Revitalization Survey as case studies. The urban–rural gap in farmers’ livelihood resilience was found to be narrowing. The rural tourism development has a significant promoting effect on enhancing the livelihood resilience of farmers. Specifically, the enhancement effect is mainly reflected in strengthening the livelihood buffering capacity, and the enhancement effect is most potent among high livelihood resilience farmers, non-poverty-stricken farmers, and farmers in the eastern region. The results of the mediation effect model indicate that livelihood factor mobility and livelihood strategy diversity are critical variables in the improvement process, with mediation effects accounting for 12.3 and 30.2%, respectively. The results of the moderation effect model further indicate that in enhancing farmers’ livelihood resilience through rural tourism development, subjective wellbeing and perceived fairness play a positive moderating role. The findings contribute to a deeper understanding of whether and how rural tourism development can enhance farmers’ livelihood resilience. We emphasize the need to develop rural tourism according to local conditions and implement precise policies to guide farmers in scientifically participating in rural tourism.